Postural sway in multiple sclerosis patients: interaction of vision, surface, and fatigue effects - Kozinc, Žiga; Žura, Eva; Brecl Jakob, Gregor (Frontiers in Human Neuroscience, 2025)
IntroductionPostural control impairments are common in patients with multiple sclerosis (MS), resulting in postural instability and increased fall risk. Sensory inputs are crucial to maintain balance adequately. Additionally, fatigue is one of the common and most disabling symptoms of MS, possibly contributing to postural deficits. Previous studies have examined the effects of fatigue and altered sensory conditions on postural control in patients with MS. The present study aimed to extend this knowledge by jointly assessing these factors within the same experimental framework, providing additional insight into how fatigue modulates sensory contributions to balance.MethodsA total of 21 patients with MS (age = 41.1 ± 10.1 years; EDSS = 1.9 ± 1.0; disease duration = 6.8 ± 4.9 years) completed balance assessments on firm and compliant surfaces with both eyes open and eyes closed, before and after a 6-min walk test used to induce fatigue. Postural sway was quantified using sway velocity and root mean square (RMS).ResultsThere was a significant effect of surface on sway velocity (p < 0.001, η2 = 0.60), with a greater sway on the compliant surface compared to the firm surface. Fatigue significantly increased sway RMS (p = 0.023, η2 = 0.23) but did not affect sway velocity (p > 0.05). The absence of visual input (eyes closed) also significantly increased sway RMS (p = 0.001, η2 = 0.46). There was a significant interaction between surface and vision for sway RMS (p < 0.001, η2 = 0.54), with a larger effect of surface instability in the eyes-closed condition.DiscussionPatients with MS face increased challenges in maintaining postural control under conditions of fatigue, surface instability, and lack of visual input. Sway RMS may be more sensitive to these effects than sway velocity.